2017
DOI: 10.29173/jchla/jabsc.v38i3.29300
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Health Libraries’ Responses to the Truth and Reconciliation Commission’s Calls to Action: A Literature Review and Content Analysis

Abstract: Introduction: As part of the Truth and Reconciliation Commission of Canada's (TRC) final report on the history and legacy of residential schools in Canada, 94 calls to action were identified. Of those, 7 are health-specific. The objective of this research paper is to determine how Canadian health library websites are responding to these calls to action. Methods: The authors conducted an initial literature review to gain an understanding of the context of Indigenous health in Canada. A content analysis of Canad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…This paper aims to fulfill a significant gap in the literature on public libraries' decolonization and reconciliation efforts by reviewing them in the context of the CFLA-FCAB (2017) Report and Recommendations. The limitations of this study are that findings are based on website content, making it difficult to assess whether these initiatives are because of the Calls to Action or CFLA-FCAB Report as it is not explicitly stated on the websites (Maestro & Chadwick 2017), and limiting them to information available on websites at the time of data collection. This paper connects to the Congress 2020 theme of confronting colonialism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper aims to fulfill a significant gap in the literature on public libraries' decolonization and reconciliation efforts by reviewing them in the context of the CFLA-FCAB (2017) Report and Recommendations. The limitations of this study are that findings are based on website content, making it difficult to assess whether these initiatives are because of the Calls to Action or CFLA-FCAB Report as it is not explicitly stated on the websites (Maestro & Chadwick 2017), and limiting them to information available on websites at the time of data collection. This paper connects to the Congress 2020 theme of confronting colonialism.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Bak, Bradford, Loyer, and Walker (2017), and Griffith (2019) discuss how Canadian archives can respond to the Calls to Action through the development of a guideline. Others focus on responses to the Calls to Action in, for example, Canadian Health Sciences libraries (Giustini 2017;Linton & Ducas 2017;Maestro & Chadwick 2017) and academic libraries (Laroque 2018, 3).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A single (primary) coder mainly completed the review of websites and thematic coding of the content, with an additional reviewer who reviewed both websites as flagged by the primary coder, and thematic categories and their labels as needed. Limitations of this research include the use of website content, which is often updated and changed, and is limited to what is made publicly available (Maestro & Chadwick 2017), the use of a single coder which has implications on the identification of and categories, and the variation in number and type of associations from each country.…”
Section: Methodsmentioning
confidence: 99%
“…Chilcott (2019) reviews Australia's ATSILIRN Protocols, the State Records New South Wales (NSW) Protocols for Staff Working with Indigenous People, the Aboriginal and Torres Strait Islander Data Archive (ATSIDA) Protocols, and the United States' Protocols for Native American Archival Materials. In a similar Canadian study, Maestro and Chadwick (2017) analyze Canadian Health Library websites for responses to TRC Calls to Action.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Here, we argue that health librarians should take actions to effect change by considering how to advance this call. Recent research has shown that health libraries are providing more information about Indigenous health to their users [5], but it is less clear the extent to which health librarians understand and value Indigenous healing practices. It is challenging to understand Indigenous health issues without exploring how they are embedded within and impacted by Indigenous knowledge systems and ways of being.…”
Section: Introductionmentioning
confidence: 99%